Role of Diversity-Focused HR Practices in Mitigating Deviant Workplace Behavior: A Review - Dr. Syed Parvaiz Ahmad Shah; Uzma Rashid Sofi (International Journal of Engineering and Management Research, 2020)
Organizations in today's scenario are faced with a large number of HRM challenges resulting from workforce diversity. Workforce diversity has become one of the most pertinent management issues in organizations from all sectors and changing workforce has required organizations to change how they think about HRM. It is quite evident that all organizations are impacted by diversity either directly or indirectly, which has made it significant for organizations to manage diversity for which HRM plays a very significant role. Thus, due to the diverse nature of workforce, it has become significant for organizations to make their HR practices diversity-oriented so that deviant workplace behaviors are reduced to minimal. It is believed that employees will not indulge in deviant workplace behaviors when they perceive their organizations to be adopting adequate and diversity-oriented HRM methods and practices. Given this contention, the purpose of this paper is to examine the role that diversity-focused HR practices play in mitigating the deviant workplace behaviors in organizations. An extensive literature review on the said constructs was conducted where both variables were studied independently and the relationship that both variables exhibit together was also studied. A systematic review of the literature was carried out with the keywords like diversity management, diversity-focused HR practices and deviant workplace behavior from several electronic databases like Google scholar, emerald insight, Springer, Taylor, and Francis.